An [(18)F]-positron emitting fluorophore allows safe evaluation of small molecule distribution in the CSF, CSF fistulas, and CNS device placement - Guo, Hua (Mol Pharm, 2019)
The small molecule fluorescein is commonly used to guide the repair of cerebral spinal fluid leaks (CSFLs) in the clinic. We modified fluorescein so that it is also visible by positron emission tomography (PET). This probe was used to quantitatively track the fast distribution of small molecules in the CSF of rats. We tested this probe in models relevant to the clinical diagnosis and treatment of central nervous system (CNS) diseases that affect CSF flow. In this study, Fluorescein was radiolabeled with fluorine-18 to produce Fc-AMBF(3). [(18/19)F]-Fc-AMBF(3) was introduced at trace quantities (13.2 nmols, 100 µCi) intrathecally (between L5 and L6) in rats to observe the dynamic distribution and clearance of small molecules in the CSF by both [(18)F]-PET and fluorescence (FL) imaging. Murine models were used to demonstrate the following utilities of Fc-AMBF(3): 1) utility in monitoring the spontaneous CSFL repair of a compression fracture of the cribriform plate and 2) utility in quantifying CSF flow velocity during neurosurgical lumboperitoneal shunt placement. Fc-AMBF(3) clearly delineated CSF-containing volumes based on noninvasive PET imaging and in ex vivo FL histology. In vivo morbidity (n = 16 rats, < 2.7 mg/kg, 77-times PET dose) was not observed. The clearance of the contrast agent from the CNS was rapid and quantitative (t(1/2)= 33.8 ± 0.6 min by FL and t(1/2)= 26.0 ± 0.5 min by PET). Fc-AMBF(3) was cleared from the CSF through the vasculature and/or lymphatic system that supplies the cribriform plate and the temporal bone. Fc-AMBF(3) can be used to diagnose CSFLs, image CSFL repair, and determine the CSF flow velocity in the CNS or through lumboperitoneal shunts by PET/FL imaging. In a conclusion, Fc-AMBF(3) PET imaging has been demonstrated to safely and dynamically quantitate CSF flow, diagnose fistulas associated with the CSF space, and approximate the clearance of small molecules in the CSF.